2018
DOI: 10.1002/marc.201800109
|View full text |Cite
|
Sign up to set email alerts
|

Polyhistidine‐Based Metal Coordination Hydrogels with Physiologically Relevant pH Responsiveness and Enhanced Stability through a Novel Synthesis

Abstract: Utilizing the abnormal physiological conditions of disease tissues can result in a site-specific functionality with high control and efficiency of stimuli-responsive hydrogels. Here, a physiologically relevant pH-responsive and self-healing hydrogel is reported based on coordination between Ni and four-arm poly(ethylene glycol)-b-polyhistidine (4PEG-PHis) that is synthesized by a novel and facile PHis preparation method using amino-terminalized four-arm PEG as the macroinitiator. Reversible PHisNi coordinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Previous studies with model poly-His peptides suggested a stable complex formation between two 6His peptides and two Ni 2+ (refs. 40,47 ). PRM-SH3-6His dimers might be the most dominant form upon Ni 2+ -induced clustering.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies with model poly-His peptides suggested a stable complex formation between two 6His peptides and two Ni 2+ (refs. 40,47 ). PRM-SH3-6His dimers might be the most dominant form upon Ni 2+ -induced clustering.…”
Section: Resultsmentioning
confidence: 99%
“…Tang e t al . utilized the coordination between Ni 2+ and four‐arm PEG to endow the hydrogel with multi‐stimuli (pH, EDTA) triggered sol–gel transition (Figure ) . Because of the exchangeable property of the coordination, Ni‐coordinated hydrogels demonstrated shear‐thinning and self‐healing properties, characterized by a decrease in viscosity upon increase in shear and near‐complete recovery between dynamic strain steps during rheological studies.…”
Section: Physical Associations To Assemble Hydrogelsmentioning
confidence: 99%
“…(b) Photographs for pH (left) and EDTA (right) triggered gel–sol transition for 4PEG‐PHis6 gel. Adapted with permission from . Copyright, 2018 Wiley.…”
Section: Physical Associations To Assemble Hydrogelsmentioning
confidence: 99%
“…These monovalent systems were not designed for tissue engineering, and as such their biocompatibility has not been fully evaluated and their stability in vivo is likely low, making them less useful for longer‐term applications . Recently, an injectable hydrogel that uses reversible poly‐histidine‐Ni coordination bonds has been used to make a multivalent biomaterial stable enough for use in sustained drug delivery systems but its in vivo suitability is yet to be proven …”
Section: Supramolecular Bonding Motifsmentioning
confidence: 99%